RELIGIOUS MODERATION IN THE PERANG TOPAT TRADITION IN LINGSAR, WEST LOMBOK, WEST NUSA TENGGARA - Saharuddin (Universitas Islam Negeri Mataram, 2024)
The Perang Topat tradition in Lingsar, West Lombok, West Nusa Tenggara, represents a unique form of religious moderation, blending Islamic and Hindu elements in a ritual that promotes harmony among different faith communities. This study examines how the Perang Topat festival fosters interreligious understanding and tolerance, addressing concerns about preserving cultural identity while maintaining mutual respect within a diverse society. The purpose of this research is to explore the ways in which this local tradition serves as a model for religious moderation, providing insights into the role of cultural rituals in uniting distinct religious groups. The study employs qualitative methods, gathering data through interviews with community leaders, participants, and observers of the Perang Topat festival. Additional data are collected through participant observation and analysis of relevant documentation related to the festival’s history and significance. Data analysis is conducted using descriptive-analytical techniques to interpret the collected information and identify patterns that illustrate the festival's role in promoting religious harmony. Findings indicate that Perang Topat serves as a symbolic representation of religious inclusivity, where shared cultural practices bridge differences between Muslim and Hindu communities, strengthening social bonds. This ritual embodies values of tolerance, cooperation, and respect for religious diversity, demonstrating that local traditions can reinforce religious moderation in multicultural contexts. The conclusion highlights that such traditions offer significant implications for promoting peace and social cohesion. The study suggests that fostering similar culturally embedded practices can serve as an effective approach to religious moderation, offering lessons that may inform broader efforts at fostering unity within pluralistic societies.